2014
DOI: 10.1590/1519-6984.22612
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the bat Sturnira lilium (Chiroptera, Phyllostomidae) in the Atlantic Forest of Rio de Janeiro, southeastern Brazil

Abstract: Bats can be monoestrous or polyestrous, and seasonal or non-seasonal in their reproductive patterns. The strategy adopted by each species or population depends on the regional climate. The objective this study was to analyze reproductive data of Sturnira lilium from long-term sampling carried out in several sites in Rio de Janeiro states, southeastern Brazil. We carried out sampling in 42 sites (with altitudes ranging from sea level to 1300 m a.s.l.) from May 1989 to December 2011. In total, we obtained 2602 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
12
0
2
Order By: Relevance
“…Over the last decades, reproductive seasonality in Neotropical bats has been assessed under ecological, behavioral, and morphological approaches [ 8 11 ]. Among them, the latter is considered more precise because involves the evaluation of morphological and functional features of reproductive organs.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, reproductive seasonality in Neotropical bats has been assessed under ecological, behavioral, and morphological approaches [ 8 11 ]. Among them, the latter is considered more precise because involves the evaluation of morphological and functional features of reproductive organs.…”
Section: Introductionmentioning
confidence: 99%
“…In Costa Rica, A. jamaicensis was reported to have a 9-month reproduction period. In southeast Brazil, Sturnira lilium was reported to have an 11-month reproduction period (Godoy et al 2014) and Platyrrhinus lineatus presented a 10-month reproduction period (Costa et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…In response to these factors, bats of the Phyllostomidae family have evolved different reproductive patterns in Neotropical regions, such as seasonal polyestry, aseasonal polyestry and monoestry (Fleming et al 1972;Estrada & Coates-Estrada 2001). Considering the high diversity of bats in this region, the available information about their reproductive biology is lacking (Zortéa 2003), and only few species have had their reproductive aspects analyzed in detail (Godoy et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Beguelini, suggested that despite some differences found in the reproductive patterns of A. planirostris, these bats do not present latency in their reproductive patterns. Likewise, Godoy, Carvalho, and Esbérard (2014), when analysing male and female S. lilium bats in the Altlantic Forest biome, concluded that they have continuous non-seasonal reproduction. It is important to remember that weather conditions (temperature and rainfall) affect food supply and consequently interfere with reproduction (Flemming et al, 1972;Heideman, 2000;Racey, 1982), and therefore, it is important to investigate the reproductive pattern in different regions.…”
Section: Artibeus Lituratus Platyrrhinus Lineatus Sturnira Liliummentioning
confidence: 99%